Security and Cryptography for Networks 7th International Conference, SCN 2010, Amalfi, Italy, September 13-15, 2010. Proceedings - Garay, Juan A.; Prisco, Roberto. (Lecture Notes in Computer Science,, 2010)
This book constitutes the proceedings of the 7th International Conference on Security and Cryptography for Networks held in Amalfi, Italy, in September 2010.